Pengembangan Alat Praktikum Tumbukan Menggunakan Mikrokontroler, Sensor Ultrasonik, dan Lintasan Air Track - Khaerul Umam; Hartono Hartono; Sulhadi Sulhadi (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
Momentum is one of the physics topics that students can better understand with practical activities. The problem found in using the ticker timer as a speed gauge in the collision practicum is that the measurement process interferes with the system being measured. This research develops a collision practicum tool using a microcontroller and ultrasonic sensor as a distance recorder. The glide track used is an air track. Based on the research conducted, it can be concluded that the collision practicum tool with a microcontroller and a glide track in the form of an air track can work well. The distance recorder or DRD is capable of recording distances every 0.2 seconds. The ultrasonic sensor as a gauge has an accuracy of 99.6% and a relative error of 0.56% for sensor 1. Meanwhile, sensor 2 has an accuracy of 99% and a relative error of 0.85%. Through the distance data obtained, it is possible to obtain an increase in momentum before and before the collision.